The Effect of Nepeta Cataria on Polyvinyl Alcohol as Blatella Germanica Cockroaches Repellent - Zulkifli, Nur Zulaikha Sahira; Yunus, muhamad Zaini (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Polyvinyl alcohol films are an environmentally friendly polymer that is widely used in packaging factoring. Nepeta Cataria essential oil consists of two isomers that are known as German cockroach repellent. This research is carried out with the objective to investigate the effect of Nepeta Cataria on polyvinyl alcohol as German cockroaches’ repellent. In this study, the essential oil is combined with polyvinyl alcohol with different concentrations from 0%, 20%, 25%, 30%, and 40% in the tensile test, FTIR test, and density test to evaluate the mechanical and physical properties of polyvinyl alcohol with essential oil. The result shows that the best repellency of German cockroaches is a 40% which is 2ml concentration of essential oil. The tensile test shows the increased concentration of essential oil the elongation at break point increases but young modulus and tensile strength decrease.